2005
DOI: 10.1007/s00264-005-0013-7
|View full text |Cite
|
Sign up to set email alerts
|

Wrist fusion versus limited carpal fusion in advanced kienbock's disease

Abstract: We treated 18 patients with advanced Kienbock's disease surgically. Six had total wrist fusions and 12 had limited carpal fusions. The average age was 39.6 yrs and the average follow up was 61.8 months and 66.8 months respectively. The visual analogue pain scores, the patient satisfaction scores and the SF 12 were better in the total wrist fusion group. The DASH (Disabilities of the Arm, Shoulder and Hand) scores, the range of movement and the grip strengths were better in the limited carpal fusions group but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 18 publications
0
10
0
5
Order By: Relevance
“…On the other hand, Tambe et al retrospectively compared 18 patients with Lichtman stages IIIB and IV who were treated with total versus limited wrist fusions. 25 The authors stated that, although pain after total wrist fusion was significantly improved compared with limited fusions, the improvement of grip strengths and the DASH scores was slightly better in the limited fusion group which has no statistical significance. As expected, the partial wrist fusion group retained some movement while the total wrist fusion group had none.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, Tambe et al retrospectively compared 18 patients with Lichtman stages IIIB and IV who were treated with total versus limited wrist fusions. 25 The authors stated that, although pain after total wrist fusion was significantly improved compared with limited fusions, the improvement of grip strengths and the DASH scores was slightly better in the limited fusion group which has no statistical significance. As expected, the partial wrist fusion group retained some movement while the total wrist fusion group had none.…”
Section: Resultsmentioning
confidence: 98%
“…Radiolunate arthrodesis, as reported by Chamay et al, is an effective procedure to relieve pain and retain some flexion/extension for treatment of degenerative radiolunate arthritis due to rheumatoid arthritis and distal radius fracture [4,5]. One disadvantage of radiolunate arthrodesis is non-union [6,7]. However, Ono reported good outcomes of radiolunate fusion using a vascularized radius graft for treatment of Bain's grade 2A Kienb€ ock disease with incongruity of the radiolunate joint [8].…”
Section: Discussionmentioning
confidence: 99%
“…31 Tambe and colleagues compared outcomes of patients treated with partial intercarpal arthrodesis and radiocarpal arthrodesis for advanced Kienböck's disease, and they found that patients treated with radiocarpal arthrodesis had improved outcomes at latest follow-up. 32 Proximal row carpectomy (PRC) is a successful salvage procedure, but the capitate head must be largely free of degenerative changes. If mild arthritic changes are present on the capitate head, an interpositional arthroplasty of dorsal wrist capsule in addition to the PRC can be effective.…”
Section: Stage 3bmentioning
confidence: 99%